Ibunda.id sebagai Layanan Mediasi dan Konsultasi Keluarga di Era Digital dalam Membentuk Keluarga Sakinah - Amriana, Amriana; Adhilah, Fizna; A, Choirunnisa Iashabilla (Jurnal Bimbingan dan Konseling Islam, 2024)
The development of digital technology has led to significant changes in patterns of social interaction and communication, including the delivery of family guidance and counseling services. This condition demands innovative counseling services that are adaptive to the needs of families in the digital era. This study aims to analyze the forms of digital-based family mediation and consultation services in fostering sakinah families on the Ibunda.id platform. This research employs a qualitative method with a descriptive approach. Data were collected through observation of the Ibunda.id platform and documentation studies derived from relevant journals and literature. Data analysis was conducted deductively by linking the concepts of mediation services, consultation services, and family counseling with empirical findings on the Ibunda.id platform. The results indicate that Ibunda.id provides individual, couple, and family counseling services that integrate digital mediation and consultation services. These services play an important role in helping individuals and families understand their problems, build healthy communication, and encourage harmonious family relationships. In addition, the use of Instagram as a medium for education and psychoeducation strengthens the role of this platform in fostering sakinah families. This study concludes that digital-based family mediation and consultation services on the Ibunda.id platform make a positive contribution to supporting the formation of sakinah families in the digital era.